Karakteristik Kuat Tekan Beton Menggunakan Serbuk Besi dengan Bahan Tambah Bestmittel - Muhammad Husein Saputra; Sartika Nisumanti; Febryandi Alfuady (Universitas Batanghari Jambi, 2026)
Concrete, a widely used building material, is prized for its exceptional compressive strength. The field of solid and sustainable infrastructure is seeing swift progress in concrete technology. Numerous ideas and innovations have emerged to enhance concrete quality, including the incorporation of iron powder as a substitute material. This substitution aims to modify concrete's characteristics and improve its strength and hardening time. The research into the compressive strength of concrete using iron powder involved an experimental technique. Findings from this research indicate that a concrete mix containing 7.2% iron powder and 0.7% bestmittel achieved a compressive strength of 28.75 MPa after 28 days. This demonstrates that both iron powder and bestmittel positively influence the compressive strength of concrete. Additionally, the optimal mixture, 7.2% iron powder combined with 0.7% bestmittel, resulted in a compressive strength of 28.75 MPa, reflecting a 3.19% increase compared to standard concrete.